Disappearance of Factor V Activity after Incubation of Plasma with Heparin and Heparinoids - Holemans, R; Vermylen, C; Verstraete, M (Thrombosis and Haemostasis, 1960)
1. Heparin and heparinoids, added to oxalated or citrated plasma produce in this plasma an inactivation of factor V; this inactivation is progressive and directly related to the length of incubation.The rate of inactivation of factor V is directly proportional to the quantity of anticoagulant added.2. When quantities with identical anticoagulant activity in the thromboplastin-calcium clotting time are compared, heparin proves to have a stronger effect than heparinoids.3. The inactvation of factor V in plasma by heparin or heparinoïds is an irreversible process, which cannot be nullified by addition of protamine sulphate.